Prevalence and determinants of reticular pseudodrusen in the Russian Ural Eye and Medical Study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Rakhimova, Ellina M.; Rusakova, Iuliia A.; Gilmanshin, Timur R.; Zainullin, Rinat M.; Panda-Jonas, Songhomitra; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Safiullina, Kamilia R.; Bolshakova, Natalia I.; Gizzatov, Ainur V.; et al. (Acta ophthalmologica, 2022)
Purpose To assess the prevalence of reticular pseudodrusen (RPD) and their determinants. Methods The Population-based Ural Eye and Medical Study conducted in Bashkortostan/Russia included 5899 participants aged 40+ years. Presence of RPDs was assessed on conventional colour fundus photographs, red-free fundus images and optical coherence tomographic images. Results The study included 4914 (83.3%) individuals (mean age: 58.5 ± 10.5 years; range: 40-94 years). Using two age limits (>55 years and 40+ years) for the definitions of RPD and AMD (age-related macular degeneration), RPD prevalence was 186/4914 (3.8%; 95% confidence interval (CI): 3.3, 4.3) and 246/4914 (5.0%, 95% CI: 4.4, 5.6), respectively, and the prevalence of any AMD without RPD was 182/4914 (3.7%: 95% CI: 3.2, 4.2) and 224/4914 (4.6%; 95% CI: 4.0, 5.1) respectively. Within the subgroup of early AMD, intermediate AMD and late AMD, RPD prevalence (age limit: 40+ years) was 55.1% (95% CI: 49.5, 60.8), 42.9% (95% CI: 33.8, 51.9) and 33.3% (95% CI: 16.4, 50.3) respectively. In multivariable analysis, higher RPD prevalence (age limit 40+ years) was associated with higher age (odds ratio (OR): 1.08; 95% CI: 1.07, 1.10; p < 0.001), rural region of habitation (OR: 3.81; 95% CI: 2.76, 5.24; p < 0.001) and lower percentage of lymphocytes on leukocyte counts (OR: 0.95; 95% CI: 0.93, 0.97; p < 0.001). Higher prevalence of any AMD without RPD was associated with urban region (OR: 1.58; 95% CI: 1.18, 2.11; p = 0.002), lower diabetes prevalence (OR: 0.55; 95% CI: 0.33, 0.90; p = 0.02) and shorter axial length (OR: 0.85; 95% CI: 0.74, 0.98; p = 0.03), after adjusting for age. Conclusions Reticular pseudodrusen (mean prevalence: 3.8% (age limit >55 years); 5.0% (age limit 40+ years)) differs from AMD without RPD in its association with urban region (AMD without RPD: rural region), lower lymphocyte percentage (AMD without RPD: no association) and a lack of associations with axial length (AMD without RPD: shorter axial length) and with diabetes prevalence (AMD without RPD: lower diabetes prevalence).
Gesehen am 22.05.2023